Farm biogas production in organic agriculture: System implications. (October 2015) - Siegmeier, Torsten; Blumenstein, Benjamin; Möller, Detlev
Abstract: Current global energy needs and the effort to substitute fossil fuels have led to extensive production of biomass in agricultural systems for purposes of renewable and more sustainable energy. At the same time, large-scale industrialized energy crop production is criticized for various sustainability issues. Organic farming systems are said to alleviate the environmental burden of agricultural production by minimizing negative externalities and generating ecological benefits. However, organic agriculture is challenged for its lower productivity. Considering this food–energy–climate nexus, a large-scale conversion of agricultural land to organic management seems infeasible. Against this backdrop, this article presents the analysis of a combined system of organic farming and biomass energy production. With a systems approach, multiple agronomic effects caused by anaerobic digestion of residue and waste biomass in organic agriculture were reviewed and transferred into a conceptual diagrammatic model of a single farm. Dimensions reviewed include nitrogen dynamics, crop yield, product quality, crop rotations, weeds, plant health, and soil fertility. The systems analysis showed that farm biogas production bears potentials to enhance overall nitrogen supply and nitrogen use efficiency and to reduce labor and energy costs of the organic farm. System implications of these agronomical effects include changes in farm productivity, stability, and resilience. Through biogas integration organic farms may contribute to renewable energy supply without additional need for land, while simultaneously increasing food output and reducing greenhouse gas emissions from livestock manure. Therefore, this study indicates possibilities for the eco-functional intensification of organic farming systems that may contribute to solving the food–energy–climate nexus. Highlights: A systems analysis of biogas production in organic agriculture (OA) was conducted. Agronomical effects of manure and residue biomass digestion were identified. Biogas integration can enhance yields/qualities and reduce nitrogen losses and GHGE. Food and environmental output of OA may be increased without additional land needs. Anaerobic digestion can contribute to "eco-functional intensification" of OA.